2017
DOI: 10.1016/j.ajur.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Benign prostatic hyperplasia and male lower urinary symptoms: A guide for family physicians

Abstract: Male patients with lower urinary tract symptoms (LUTS) and benign prostatic hyperplasia (BPH) are increasingly seen by family physicians worldwide due to ageing demographics. A systematic way to stratify patients who can be managed in the community and those who need to be referred to the urologist is thus very useful. Good history taking, physical examination, targeted blood or urine tests, and knowing the red flags for referral are the mainstay of stratifying these patients. Case selection is always key in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 3 publications
(4 reference statements)
0
14
1
1
Order By: Relevance
“…13,14 Age related LUTS\BPH was mentioned by Weiyu Zhang et al while beside the age related LUTS, the role of the medical management of BPH and decreasing the resultant LUTS were also reported by Farhad Fakhrudin and colleagues. 15,16 Improvement of LUTS and inconsequence depression, anxiety and psychiatric morbidity was documented for both medical and surgical treatment by Kia Fatt Quek et al (in the contrary of our study). 17 Finally, Kia Fatt Quek et al in another study, supported our thoughts about the superiority of TURP in minimizing psychological morbidities in patients with LUTS secondary to BPH.…”
Section: Discussioncontrasting
confidence: 49%
“…13,14 Age related LUTS\BPH was mentioned by Weiyu Zhang et al while beside the age related LUTS, the role of the medical management of BPH and decreasing the resultant LUTS were also reported by Farhad Fakhrudin and colleagues. 15,16 Improvement of LUTS and inconsequence depression, anxiety and psychiatric morbidity was documented for both medical and surgical treatment by Kia Fatt Quek et al (in the contrary of our study). 17 Finally, Kia Fatt Quek et al in another study, supported our thoughts about the superiority of TURP in minimizing psychological morbidities in patients with LUTS secondary to BPH.…”
Section: Discussioncontrasting
confidence: 49%
“…The score gives an idea of the severity of LUTS and the most bothersome symptoms. On follow-up, the score can give accurate documentation of patients' progression and deterioration [65].…”
Section: Discussionmentioning
confidence: 99%
“…BPH is a progressive disease with a frequency that successively increases mainly after the age of 50. [1][2][3][4][5][6] This study showed that patients aged 60 to 69 were predominant. Complications of BPH can occur immediately, but they can also occur after many years of the onset of the first symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the obstruction itself (in this case caused by enlargement of the prostate) causes neural changes on the detrusor that further contribute to the formation and development of symptoms of clinical (symptomatic) BPH. [1][2][3][4][5][6] The aim of this study is to analyse the frequency of typical complications in the treatment of patients with benign prostatic hyperplasia and the effect of medicamentous treatment in groups patients with two different stages of BPH.…”
Section: Methodsmentioning
confidence: 99%